Correlation of Radiographic and Pathologic Findings of Dermal Lymphatic Invasion in Head and Neck Squamous Cell Carcinoma - Spector, M.E. (American Society of Neuroradiology, 2012)
HNSCC that involves the skin is able to invade the dermal lymphatic system. Currently there is no way to identify patients with dermal lymphatic invasion preoperatively. The purpose of this study is to determine whether CT can predict dermal lymphatic invasion. Medical records, CT scans, and corresponding histopathologic slides were reviewed of HNSCC patients with skin resected as part of their treatment. Dermal lymphatic invasion was defined radiographically as linear reticulations of the dermis and subcutaneous fat adjacent to the tumor. Twelve patients were identified with imaging suggestive of dermal lymphatic invasion. The corresponding pathology slides showed only 1 of the 12 patients had dermal lymphatic invasion, whereas the other 11 specimens showed peritumoral inflammation without evidence of tumor invasion. This study demonstrates that the linear areas of reticulation are most commonly caused by peritumoral inflammation and are not due to dermal lymphatic invasion.